2020
DOI: 10.3390/microorganisms8060881
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production in Soil Environments—Anaerobic Biogeochemistry and Microbial Life between Flooding and Desiccation

Abstract: Flooding and desiccation of soil environments mainly affect the availability of water and oxygen. While water is necessary for all life, oxygen is required for aerobic microorganisms. In the absence of O2, anaerobic processes such as CH4 production prevail. There is a substantial theoretical knowledge of the biogeochemistry and microbiology of processes in the absence of O2. Noteworthy are processes involved in the sequential degradation of organic matter coupled with the sequential reduction of electron accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 119 publications
5
54
0
Order By: Relevance
“…About 70–80% of CH 4 is generated biologically and a large part of it is removed in the stratosphere and troposphere through reactions with chlorine and ⋅ OH radicals ( Le Mer and Roger, 2001 ). In addition, microbial methane oxidation is an important terrestrial methane sink ( Conrad, 2020 ). Bacteria can convert CH 4 to methanol aerobically using the enzyme methane monooxygenase (MMO; Conrad, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…About 70–80% of CH 4 is generated biologically and a large part of it is removed in the stratosphere and troposphere through reactions with chlorine and ⋅ OH radicals ( Le Mer and Roger, 2001 ). In addition, microbial methane oxidation is an important terrestrial methane sink ( Conrad, 2020 ). Bacteria can convert CH 4 to methanol aerobically using the enzyme methane monooxygenase (MMO; Conrad, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study site in Vercelli (Italy) has a history of rice cultivation for over a century (Ferrero and Vidotto 2010 ) and thus, these soils have been exposed to many cycles of flooding and drainage. Over time, a soil community has been selected that is adapted to these conditions (Conrad 2020 ). It has been shown that microbial communities in rice fields stayed rather stable after drainage or re-flooding and even methanogenic archaea did not decrease considerably in numbers after desiccation and oxygen exposure (Breidenbach et al 2016 , Liu et al 2018 , Conrad 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, a soil community has been selected that is adapted to these conditions (Conrad 2020 ). It has been shown that microbial communities in rice fields stayed rather stable after drainage or re-flooding and even methanogenic archaea did not decrease considerably in numbers after desiccation and oxygen exposure (Breidenbach et al 2016 , Liu et al 2018 , Conrad 2020 ). This agrees with our study and the observation that the overall microbial composition in the bulk soil was only weakly affected by the different water management.…”
Section: Discussionmentioning
confidence: 99%
“…The water content of soils directly affects O2 availability, which, in turn, is a fundamental factor shaping CH4-cycling community composition. O2 diffuses more slowly in water-saturated soils, which thus have lower O2 availability [56].…”
Section: Spatio-temporal Dynamics In Methane-cycling (Micro-)biomementioning
confidence: 99%